Shorebirds Affect Ecosystem Functioning on an Intertidal Mudflat - Booty, James M.; Underwood, Graham J. C.; Parris, Amie; Davies, Richard G.; Tolhurst, Trevor J. (Frontiers in Marine Science, 2020)
Ecosystem functioning and services have provided a rationale for conservation over the past decades. Intertidal muddy sediments perform crucial functions, including erosion protection, nutrient cycling and carbon sequestration. Key mediators within this system include microphytobenthic biofilms, which bind sediment and influence nutrient biogeochemistry, and wading birds which feed extensively on sediment dwelling infauna, which in turn graze biofilms. Some wader species, specifically small sandpipers, have recently been found to interact directly with biofilms, e.g. by grazing, adding complexity to this food web. It has been suggested that infauna grazing by waders may lead to a reduction in biofilm grazing pressure by infauna. If this was the case it would likely have significant top-down, trophic cascade effects on key mudflat ecosystem functions. We carried out an exclusion experiment on the Colne Estuary, Essex, UK to examine whether wader presence significantly affects sediment erodibility, microphytobenthos fluorescence (Fo) and sediment-water nutrient fluxes (nitrate, nitrite, ammonia, phosphate and dissolved organic carbon (DOC)). Excluding wading birds caused significant changes in regulating and provisioning ecosystem functions, including mudflat erodibility and nutrient fluxes (with the exception of DOC). Fo was significantly greater, sediment critical shear strength increased, and the magnitude of nutrient fluxes increased where waders were absent. Excluding waders did not cause a significant difference in infauna density within the sediment, suggesting that a trophic cascade was not the cause of the measured effects. The dominant wading species at the site, dunlin Calidris alpina, is reported to consume biofilm and is considered to play a key role in maintenance of ecosystem stability on mudflats. After a period of 23 days, the arrival of the mud snail Peringia ulvae appeared to compensate for the absence of waders, consuming biofilm and causing a reduction in surface biofilm differences between presence/absence plots. This study introduces a previously unknown effect of wader foraging and bioturbation within this system, and highlights an area of wader science which could aid joint conservation and human provisioning action.